2009
DOI: 10.1016/s0973-0508(09)80022-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for cerebral contusions: Rationale and practice

Abstract: While the indications for surgery in extra- and subdural hematomas are relatively established, the role, timing and the indications for the surgical treatment of cerebral contusions remains nebulous. The pathophysiology of brain edema and the resultant increase in intracranial pressure due to brain contusions is discussed. The role and limitations of early evacuation of contused brain are considered in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Here blunt injury is investigated and we are concerned primarily with the brain's pressure response, as intra-cranial pressure is regarded as a good indicator of injury severity and has been linked to the onset of cerebral contusions [11] , [16] , i.e. focal lesions characterised by tissue rupture and cortical bleeding [17] [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Here blunt injury is investigated and we are concerned primarily with the brain's pressure response, as intra-cranial pressure is regarded as a good indicator of injury severity and has been linked to the onset of cerebral contusions [11] , [16] , i.e. focal lesions characterised by tissue rupture and cortical bleeding [17] [19] .…”
Section: Introductionmentioning
confidence: 99%
“…9 The benefits of removing the contused brain include the removal of edema producing osmotic load and abolition of necrotic and apoptotic cascades triggered off by blood degradation products. 10 Contusion evacuation benefits patients of severe head injury with contusion and intractable intracranial hypertension. 11 The survival and functional outcome after these procedures are acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent randomized trial have shown that long-term outcome is worse for decompressive craniotomy. 15 The benefits of removing the contused brain include the removal of edema producing osmotic load and abolition of necrotic and apoptotic cascades triggered off by blood degradation products 16 ( Fig. 2a and b).…”
Section: Discussionmentioning
confidence: 99%